Calmodulin Regulated Spectrin Associated Protein 1 mRNA is Directly Regulated by miR‐126 in Primary Human Osteoblasts. Issue 7 (5th January 2017) - Strassburg, Sandra; Nabar, Nikita; Lampert, Florian; Goerke, Sebastian M.; Pfeifer, Dietmar; Finkenzeller, Günter; Stark, Gerhard B.; Simunovic, Filip
ABSTRACT: Vascularization is essential for bone development, fracture healing, and bone tissue engineering. We have previously described that coculture of primary human osteoblasts (hOBs) and human umbilical vein endothelial cells (HUVECs) improves differentiation of both cell types. Investigating the role of microRNAs (miRNAs) in this system, we found that miR‐126 is highly upregulated in hOBs following coculturing with HUVECs. In this study we performed miR‐126 gain‐of‐function and loss‐of‐function experiments in hOBs followed by microarray analysis in order to identify targets of miR‐126. The transcript cluster IDs were sieved by applying cut‐off criteria and by selecting transcripts which were upregulated following miR‐126 downregulation and vice versa. The calmodulin regulated spectrin associated protein 1 (CAMSAP1) mRNA was confirmed to be differentially regulated by miR‐126. Using the luciferase reporter assay it was demonstrated that CAMSAP1 is directly targeted by miR‐126. In this study, we show that miR‐126 and CAMSAP1 directly interact in hOBs. This finding has potential implications for tissue engineering applications. J. Cell. Biochem. 118: 1756–1763, 2017. © 2016 Wiley Periodicals, Inc. Abstract : This article investigates the targets of miR‐126 in osteoblasts. Using gain‐of‐function and loss‐of‐function experiments followed by Microarrays we identify potential candidates. The calmodulin regulated spectrin associated protein 1 is confirmed as a direct target of miR‐126 in osteoblasts.